Polymorphism in the PPARgamma2 and beta2-adrenergic genes and diet lipid effects on body composition, energy expenditure and eating behavior of obese women - Rosado, Eliane Lopes; Bressan, Josefina; Martins, Marta F.; Cecon, Paulo R.; Martı́nez, Jose Alfredo (Appetite, 2007)
In order to evaluate the effect of polymorphism in the PPARgamma2 and beta2-adrenergic genes and diet lipids on body composition, energy expenditure and eating behavior of obese women, 60 subjects were submitted to anthropometric, biochemical, dietary, molecular, basal and postprandial metabolism (indirect calorimetry) and eating behavior (visual analog scale) evaluation. Fat and saturated fatty acid (SFA) high diet was used to assess postprandial metabolism. The frequency of Pro12Pro/Gln27Gln, Pro12Pro/Gln27Glu, Pro12Pro/Glu27Glu and Pro12Ala/Gln27Glu genotypes was 35.71%, 30.37%, 23.21% and 10.71%, respectively. These values were not significant (p>0.05) for the dietary, anthropometric, biochemical and metabolic parameters. The Pro12Ala/Gln27Glu group was found to present greater energy used in postprandial period (EUPP). The presence of the PPARgamma2 gene variant, independent of beta2-adrenergic gene polymorphism, resulted in fat oxidation increase. Also, this group presented higher satiety, compared to the Pro12Pro/Gln27Gln group. The presence of the variant alleles in the PPARgamma2 gene suggests benefits in food intake control.
Keywords: Obesity; PPARgamma2; Beta2-adrenergic receptor; Diet; Energy metabolism; Eating behavior